2002
DOI: 10.1111/j.0004-8666.2002.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the short‐term outcomes of hysterectomy with and without oophorectomy

Abstract: Although levels of satisfaction with the procedure of hysterectomy were high, new symptoms and regrets about the loss of fertility were commonly reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…While hysterectomy seems to have no systematic negative effect on orgasmic potential in most women, a subgroup of 15-25% appears to experience adverse changes in the frequency of orgasm [21,39,62,66,69].…”
Section: Orgasmmentioning
confidence: 89%
See 3 more Smart Citations
“…While hysterectomy seems to have no systematic negative effect on orgasmic potential in most women, a subgroup of 15-25% appears to experience adverse changes in the frequency of orgasm [21,39,62,66,69].…”
Section: Orgasmmentioning
confidence: 89%
“…To date, empirical evidence does not support any broad adverse effects of hysterectomy on women's psychosocial functioning [5]. Positive outcomes of hysterectomy include decreases in chronic pelvic pain and pain during intercourse, as well as the elimination of menstrual pain and dysfunctional uterine bleeding [21,23,54]. However, hysterectomy may sometimes result in new symptoms related to pain, sexual dysfunction, and psychological distress, as well as in long-term adverse effects related to ovarian failure [39,47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were predominately Caucasians from a homogenous socioeconomic population. Mean age was [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Mean parity was 1.65 (range, 0-4) children and six patients reported that they had undergone primary sphincter repair at the time of delivery.…”
Section: Patientsmentioning
confidence: 99%